Semantic Organizacion of The Synonymic Sets - Grdzelyan, Rouzan (Bulletin of Yerevan University H: Russian Philology, 2025)
The article examines the Russian and Armenian synonymic sets from the point of view of their semantic organization. We put forward a hypothesis that the basis of the semantic mechanisms for the formation of synonyms is the idea of ​​semantic patterns. Features associated with the predominance of certain patterns in a language can be considered a typological characteristic of a given language. Thus, the relevance of such a topic is due to the desire to consider the traditional problem of synonymy from a different point of view, in the context of a different scientific approach to synonymy as a semantic mechanism of identity, to the ability of a language to generate self-similar models. This approach can contribute to the development of new research methods in the field of theoretical linguistics and lexical typology. The study examines synonyms within the framework of their traditional presentation in the form of a synonymic sets and makes an attempt to describe them as a certain semantic, conceptual whole, consisting of words / meanings of words, semantic components that have a certain organization and are in certain relationships. By analogy with the semantic field, the synonymic sets also has a component or components that is obligatory for all words of the series - the semantic core, as well as a number of additional, optional semantic elements. Thus, a synonymic sets may include words with the same set of semantic components. The number of similar words indicates a low or, conversely, high degree of recurrence of synonyms with the same set of semantic components. A synonymous series as a conceptual space can include a different set of optional semantic components, that is, have a greater or lesser degree of detail in the semantic structure - different nominative density. It seems that the description of the synonymic sets from this point of view is most effective for identifying typological differences between groups of synonyms in two languages.
Keywords: synonymic set; semantic organization; recurrence; nominative density; semantic pattern